Implementasi Metode Weighted Aggregated Sum Product Assesment Untuk Vaksin Polio Terhadap Balita Studi Kasus Puskesmas Masat - Suaihera Rahma Yunia; Eko Suryana; Desi Mahdalena (Jurnal Media Infotama, 2025)
Providing polio vaccine to toddlers is a very important preventive measure in efforts to prevent polio disease, especially in areas with limited health access such as Masat Public Health Center. However, in its implementation, an appropriate decision-making method is needed to determine the priority of toddler vaccination based on various relevant criteria. This study implements the Weighted Aggregated Sum Product Assessment (WASPAS) method as a tool in multi-criteria decision-making related to polio vaccine administration. This method combines two approaches, namely the Weighted Sum Model (WSM) and the Weighted Product Model (WPM), to provide more accurate and flexible results. The criteria used in this study include the age of the toddler, health history, previous immunization status, and environmental factors. The results of the analysis show that the WASPAS method is able to provide objective vaccination priority recommendations and can be applied as a decision support system in the Puskesmas environment. Thus, it is hoped that this method can help increase the effectiveness of vaccine distribution and reduce the risk of polio spread among toddlers.